Parameters that affect the photodegradation of dyes and pigments in solution and on substrate – An overview. (February 2023) - Groeneveld, Iris; Kanelli, Maria; Ariese, Freek; van Bommel, Maarten R.
Abstract: It has been known for many years that dyes and pigments are subject to light-induced degradation, or photodegradation, when exposed to light. It is the very reason why some beverages or medicines are wrapped in light-tight packaging materials, and why museums cover their windows with UV-blocking filters. The exact chemistry of light-induced degradation can be quite complex. Why and how are these dyes and colorants affected by light? How fast do these processes occur? Are there ways to prevent this from happening in a straight-forward and durable way? These were and still are questions that are relevant to the many fields where colorants are applied. In order to support these questions, we have tried to provide a broad overview of the research that has already been conducted on photodegradation of dyes and pigments and the analysis of photodegradation products. In those papers, the most important parameters that were discussed are the influence of the irradiation source, intensity and time, the presence or absence of oxygen, temperature, the effects that catalysts have, as well as the dye or pigment concentration. Additionally, we have investigated the differences found for photodegradation in solution and on substrates and specific parameters that may affect the processes in these media. Highlights: An increase in the light dose leads to increased photodegradation. The effect of the wavelength is associated with the structure of the dye/pigment. The presence of oxygen influences the photodegradation rate and mechanism. Temperature influences photodegradation less compared to other parameters. Photodegradation mechanisms in-solution may differ from those on substrates.